An empirical investigation on dollarization and currency devaluation: A case study of Tanzania - Zakia Musoke (Kiel Institute for the World Economy (IfW), 2017)
The debate regarding the usage of domestic currency versus dollarizing an economy is still robust in many developing countries. Dollarizing an economy commonly entails dollarizing bank deposits and loans, transacting in dollars and tagging prices of goods and services in dollar. In Tanzania, commercial banks have the power to open foreign currency deposit accounts for any account holder, giving them the freedom to hold foreign currency and pay in foreign currency. Due to the strength of foreign currencies over the domestic shilling, investors prefer to hold bank accounts in foreign currencies preferably USD. This paper's main focus is dollarization and currency devaluation; of which are yet unresolved both theoretically and empirically. Using monthly nominal exchange rate data for the study period 2000-2014, the author introduced GARCH models to examine the relationship between dollarization and exchange rate. The Autoregressive Conditional Heteroscedasticity models indicate that dollarization does indeed induce currency depreciation as well as exchange rate volatility. Based on the findings and conclusions from other literature, this paper also proposes measures on how the country can prevent or offset the negative impacts of dollarization.
Keywords: C8; E5; E41; 330; Dollarization; currency devaluation; GARCH; exchange rates